Integrated Geophysical-Geological 3D Model of the Right-Bank Slope Downstream from the Rogun Dam Construction Site, Tajikistan - Hans-Balder Havenith; Isakbek Torgoev; Anatoli Ischuk (International Journal of Geophysics)
In summer of 2015 we had completed a geophysical survey complemented by borehole drilling near the right-bank slope of the Rogun Dam construction site, Tajikistan. These data were first processed and then compiled within a 3D geomodel. The present paper describes the geophysical results and the 3D geomodel generated for an ancient mass movement located immediately downstream from the construction site. The geophysical survey included electrical and seismic profiles and ambient vibration measurements as well as earthquake recordings. The electrical and seismic data were processed as tomographic sections, the ambient vibrations as horizontal-to-vertical spectral H/V ratios, and the earthquake data mainly in terms of standard spectral ratios. By estimating the average shear wave velocities of the subsurface, we computed the local soft layer thickness from the resonance frequencies revealed by the H/V ratios. Three seismic stations had been installed for ten days along a profile crossing the intermediate plateau. Standard spectral ratios inferred from ten processed earthquake measurements confirmed the presence of a thick soft material layer on the plateau made of weathered rocks, colluvium, and terrace deposits, which produce a medium-level amplification at about 2 Hz. The 3D geomodel was first built on the basis of new topographic data, satellite imagery, and a geological map with two sections. Then, the various electrical resistivity and seismic refraction tomographies were inserted in the geomodel. The soft layer thickness information and borehole data were represented in terms of logs in the model. The site is crossed by the Ionakhsh Fault that could be modeled on the basis of the geological inputs and of a lateral resistivity gradient found on one electrical profile along the steep lower slope. The integrated interpretation of all results reveals that probably only a relatively small part of the ancient giant mass movement is really exposed to slope instability phenomena.